BIM – CONSTRUCTION LIFECYCLE - Kumar, Nirmal; Singh, Deeksha; Kumar, Bipasha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Engineering, construction, and architecture have all been impacted by building information modeling, or BIM. The use of BIM technology during a building’s operational phase is only now beginning to gain popularity among building owners looking for creative ways to increase the effectiveness of their facility operations. Lifespan The process of creating, storing, and using building data to manage operations and maintenance of buildings over the course of their operational lives is known as building information modeling, or BIM. Many facets of building operations that gain from improved data are of interest to facility managers. The goal is for stakeholders to produce and utilize consistent digital information at every stage of the asset’s lifecycle. BIM Lifecycle is the process of creating, utilizing and maintaining the building information. BIM technology has the potential to significantly increase the efficiency of project maintenance as well as building design, production, construction, operation, and maintenance. Specifically, information management throughout the manufacturing stage optimizes the production process, and collaborative design using BIM technology improves design efficiency. Its data management function increases the effectiveness of building operations and maintenance, and its 3D visualization tool lowers construction errors and encourages efficiency in the constructing phase.